ANALISIS DIMENSI KUALITAS LAYANAN PERIZINAN PADA KANTOR ADMINISTRASI PERIZINAN KOTA MAKASSAR - Maryadi Maryadi (AkMen JURNAL ILMIAH, 2011)
This study was aimed analyze the approval service deminsions in Approval Adminstration Service office of Makassar. This study used descriptive method, this method was considered appropriate wih the need obtaining accurate data and information according to studied variables. Data were collected by using questionnaire, and the number of sample studied were the existing approval requests, managed by approval service office of Makassar. Study results indicate the followings: (1) Evaluating results for service dimension including tangibility, reliability, responsiveness, empathy and assurance indicated that majority of responedents showed that evaluation for approval service was not satisfying, (2) Reliability dimension need to be provided with serious attention because this service dimension get most attention from customers or the approval applicants, particularly the procedural mechanisms and approval requirements which were reported by most of respondents less satisfying, this was due to the service provided was likely complicated and the approval administration process considered to consume much time. From this findings, it was suggested to contemplate efforts for the improvement of the approval service.